Characterising demographics, knowledge, practices and clinical care among patients attending sickle cell disease clinics in Eastern Uganda - Olupot-Olupot, P; Wabwire, H; Ndila, C; Adong, R; Ochen, L; Amorut, D; Abongo, G; Okalebo, CB; Akello, SR; Oketcho, JB; Okiror, W; Asio, S; et al. (F1000Research, 2020)
Background: In Uganda to date, there are neither established registries nor descriptions of facility-based sickle cell disease (SCD) patient characteristics beyond the central region. Here, we summarize data on the baseline clinical characteristics and routine care available to patients at four clinics in Eastern Uganda as a prelude to a clinical trial. Methods: Between February and August 2018, we conducted a cross-sectional survey of patients attending four SCD clinics in Mbale, Soroti, Atutur and Ngora, all in Eastern Uganda, the planned sites for an upcoming clinical trial (H-PRIME: ISRCTN15724013). Data on socio-demographic characteristics, diagnostic methods, clinic schedules, the use of prophylactic and therapeutic drugs, clinical complications and patient understanding of SCD were collected using a structured questionnaire. Results: Data were collected on 1829 patients. Their ages ranged from 0 to 64 years with a median (IQR) of 6 (3-11) years. 49.1% of participants were male. The majority (1151; 62.9%) reported a positive family history for SCD. Approximately half knew that SCD is inherited from both parents but a substantial proportion did not know how SCD is transmitted and small numbers believed that it is acquired by either transfusion or from other people. Only 118/1819 (6.5%) participants had heard about or were using hydroxyurea while 356/1794 (19.8%) reported stigmatization. Participants reported a median of three (IQR 1-4) hospital admissions during the preceding 12 months; 80.8% had been admitted at least once, while 14.2% had been admitted more than five times. Pain was the most common symptom, while 83.9% of those admitted had received at least one blood transfusion. Conclusion: The majority of patients attending SCD clinics in Eastern Uganda are children and few are currently being treated with hydroxyurea. The data collected through this facility-based survey will provide background data that will be useful in planning for the H-PRIME trial.